Analysis and Allocation of Cancer-Related Genes Using Vague DNA Sequence Data - Aslam, Muhammad; Albassam, Mohammed (Frontiers in Genetics, 2022)
To test the equality of several independent multinomial distributions, the Chi-square test for count data is applied. The existing test can be applied when complete information about the data is available. The complex process such as DNA count, the existing test under classical statistics may mislead. To overcome the issue, the modification of the Chi-square test for multinomial distribution under neutrosophic statistics is presented in this paper. The modified form of Chi-square test statistic under indeterminacy/uncertainty will be presented and applied using the DNA count data. From the DNA count data analysis, simulation and comparative studies, the proposed test is found to be informative, springy, and goodish as compared to the existing tests.